Implementing TB-Stigma reduction interventions in High Burden Countries: a perspective on a conceptual framework - Bibi, Bushra; Goodall, Mark; Ranjit, Injety; Jones, Stephanie; Miller, Colette (Frontiers in Tuberculosis, 2025)
Tuberculosis (TB) is a preventable, curable disease but still impacts people in high-burden countries, who face challenges, including stigma, in accessing and engaging with healthcare services. The Nuttall's review examined the quality of existing TB-stigma intervention studies and developed a conceptual framework of pathways to stigma reduction. We critically appraised the methods used and expanded upon these findings in the context of the WHO End TB Strategy. The included studies showed significant heterogeneity in design, aims, populations, type of TB-stigma targeted and took place across diverse countries. Only three of 11 studies were rated as high quality. This systematic review synthesized existing interventions and outcomes into a conceptual framework outlining pathways to reduce TB-stigma. The conceptual framework highlights the need for educational, emotional, and psychosocial support for TB patients, Health Care Workers, and Communities, and provides a useful guide of pathways needed in TB-stigma reduction interventions. However, to be effective, stigma reduction interventions must be part of a well-organized, and committed multi-sectoral collaboratives, which extend beyond national and global TB programs, including mental health services, social support systems, and public health programs.